KULTURELLE HORISONTER PÅ BØRNS UDVIKLING OG SOCIALISERING - Nielsen, Pia Løvschal (Tidsskriftet Antropologi, 1998)
Pia Løvschal Nielsen: Cultural Aspects of Child Development and Socialisation Using ethnographic material from a Hutterite colony in Western Canada, the article shows how adult interpretations of child development and socialisation influence the organisation of children’s daily routines and thus their access to social and cultural knowledge. In this colony, adults are thought to occupy a central position in children’s social and cultural learning processes. At the same time, adults and children are seen as two exclusive categories with separate spheres of action. Daily routines, grounded in this cultural construction, actively exclude children from adult practices, minimising their daily participation in adult spheres of action and allowing few opportunities for direct observation of adult models. The author discusses how children’s cultural and social learning takes place through exclusion from, rather than participation in, adult practices. Hutterite children’s intense involvement in an annual community event indicates that children actively create and participate in their own social field gaining social and cultural knowledge through this process rather than through engagement with adults. The author argues that children’s cultural learning processes are far more active and situational than proposed by theories of development and intemalisation which identify adults as focal to children’s development and intemalization of cultural codes for agency.